What the Agricultural Sector in Florida Needs to Know about Heat-Related Illness (HRI) - Paul Monaghan; Karissa Raskin; Maria Morera; Jose Antonio Tovar Aguilar; Valerie Mac; Joan Flocks (EDIS)
Heat-related illness (HRI) can range from rashes, fainting, and cramps to heat exhaustion and heat stroke. It can be fatal, and all outdoor workers in agriculture (as well as those in high-heat indoor settings such as greenhouses) are at risk. This new 6-page publication of the UF/IFAS Department of Agricultural Education and Communication provides basic information on how to recognize the symptoms of HRI, on the underlying physiological processes and related risk factors, and on how to treat it.  This publication also provides a list of preventative measures that growers, supervisors, and agricultural workers can follow, along with links to additional resources. Written by Paul Monaghan, Karissa Raskin, Maria Morera, Antonio Tovar, Valerie Mac, and Joan Flocks. https://edis.ifas.ufl.edu/wc359